The Influence of Perceived Benefits, Trust, Service Quality, Price Perception, and Sustainable Consumption Behavior on Customer Satisfaction and Repurchase Intention - Sri Wahyuni; Janfry Sihite (Journal of Sustainable Economic and Business, 2026)
This study aims to analyze the influence of service quality, trust, price perception, sustainable consumption behavior, and perceived benefits on customer satisfaction and repurchase intention among Islamic life insurance customers. The primary issue addressed in this study concerns how these factors shape customer satisfaction and repurchase loyalty in the insurance industry. This research employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with data analysis conducted through SmartPLS software. The findings indicate that service quality, trust, and price perception have a positive and significant effect on customer satisfaction. Perceived benefits have a positive effect at the 10% significance level, while sustainable consumption behavior shows a significant but negative effect on customer satisfaction. Furthermore, customer satisfaction has a positive and highly significant effect on repurchase intention. These findings confirm that customer satisfaction plays a central role in building customer loyalty. Therefore, improving service quality, strengthening trust, and ensuring fair price perception represent key strategic priorities in enhancing customers’ repurchase intention in Islamic life insurance services.